Challenges and opportunities for ICT adoption in agricultural extension - Agwu, Ekwe; Uchechi, Nwokorie (Technical Centre for Agricultural and Rural Cooperation, 2019)
With the majority of extension personnel in Nigeria having access to computers, telephones and radio equipment, more farmers are being reached with agricultural information than ever before. However, challenges of inclusion and affordability remain.